1981
DOI: 10.1136/thx.36.10.787
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral salbutamol and slow-release aminophylline on exercise tolerance in chronic bronchitis.

Abstract: In a double-blind placebo-controlled trial in 24 patients fulfilling the MRC criteria for chronic bronchitis, oral salbutamol 4 mg and slow-release aminophylline (Phyllocontin)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
2

Year Published

1984
1984
2002
2002

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 10 publications
0
15
0
2
Order By: Relevance
“…However, only few studies have shown significant ameliorations in the absence of bronchodilatation [18,19]. Other studies in COPD patients [22,41] and healthy sub jects [23] did not find any changes in exer cise variables or the observed modifica tions were associated with bronchodilata tion [17],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only few studies have shown significant ameliorations in the absence of bronchodilatation [18,19]. Other studies in COPD patients [22,41] and healthy sub jects [23] did not find any changes in exer cise variables or the observed modifica tions were associated with bronchodilata tion [17],…”
Section: Discussionmentioning
confidence: 99%
“…For sympa thomimetic amines the mechanism and the site of action are more controversial, al though evidence indicates that these drugs have a positive inotropic effect on muscle contractility through cyclic AMP [15]. Some studies have demonstrated an im provement in exercise performance [16][17][18], dyspnea [19] and respiratory muscle fatigue after ingestion of theophylline [I, 2, 4, 6, 9, 13], while several others failed to find similar modifications [5,[20][21][22][23][24][25][26][27][28][29]. The present experiment was aimed at in vestigating the effects of the acute infusion of aminophylline (A) and the selective p2-sympathomimetic agent, salbutamol (S), at therapeutic doses on the strength and endurance of unfatigued skeletal and ventilatory muscles in normal humans.…”
Section: Introductionmentioning
confidence: 99%
“…Such relief of breathlessness has already been demonstrated in patients with COPD receiving theophylline and is usually attributed to the bronchodilator effect of the drug [ 12], Since breathlessness is a distressing symptom and contributes to limit exercise performance, it is important that both beta-agonists were shown to decrease dyspnea after a test (6MD) which corre sponds quite closely to the demands of everyday activities [25]. Beta-agonists thus lessen breathlessness as shown by change in the dyspnea score (VAS).…”
Section: Discussionmentioning
confidence: 99%
“…These drugs may influence various factors con tributing to lung function and exercise tol erance [7][8][9][10][11]. It has been suggested that, in patients with COPD, improvement in airways obstruction after inhaling bronchodilators may not accurately reflect clinical benefit as assessed by exercise tests [12]. Since breathlessness and limitation of exercise tolerance are major factors con tributing to disability in patients with ad vanced COPD, we used a measurement of the distance covered in 6-min walking (6MD) and the scores of breathlessness on a visual analogue scale (VAS) and subjec tive rating of perceived exertion (RPE) as Recently, a new bronchodilator has been tested in patients with COPD, and it has been shown that for inhalation ther apy it is potent and selective without side effects [13].…”
Section: Introductionmentioning
confidence: 99%
“…This improvement in walking distance with placebo was similar to that found by Leitch and his colleagues with oral aminophylline. 22 Nietrzeba and his colleagues, who used intravenous aminophylline, showed a similar improvement in maximum work in a group of patients with chronic obstructive bronchitis (unfortunately, there was no placebo study), but they failed to show any improvement in forced expiratory volume in one second or peak expiratory flow rate to either aminophylline or inhaled isoetharine (0-68 mg).29 They did show, however, an improvement in maximal inspiratory flow rate.…”
mentioning
confidence: 95%